Insulin signaling as a potential natural killer cell checkpoint in fatty liver disease. Issue 3 (14th February 2018) - Amer, Johnny; Salhab, Ahmad; Noureddin, Mazen; Doron, Sarit; Abu‐Tair, Lina; Ghantous, Rami; Mahamid, Mahmud; Safadi, Rifaat
Abstract : Insulin resistance is a key risk factor in the progression of nonalcoholic fatty liver disease (NAFLD) and may lead to liver fibrosis. Natural killer (NK) cells are thought to exert an antifibrotic effect through their killing of activated hepatic stellate cells (HSCs). Here, we investigated how the interplay between NK cells and HSCs are modified by insulin resistance in NAFLD. Fresh peripheral blood NK cells (clusters of differentiation [CD]56 dim, CD16 + ) were collected from 22 healthy adults and 72 patients with NAFLD not currently taking any medications and without signs of metabolic syndrome. NK cells were assessed for insulin receptor expressions and cytotoxic activity when cultured in medium with HSCs. Fibrosis severities in patients with NAFLD were correlated linearly with elevated serum proinflammatory cytokine expression and insulin resistance severity. At the same time, fibrosis severities inversely correlated with insulin receptor expressions on NK cells as well as with their cytotoxic activities determined by CD107a by flow cytometry. NK cells from donors exhibiting severe fibrosis and insulin resistance exhibited significant mammalian target of rapamycin and extracellular signal‐regulated kinase depletion (through NK cell western blot quantitation), increased apoptosis, and failure to attenuate HSC activation in vitro . While exposure to insulin stimulated the cytotoxic activity of healthy NK cells, rapamycin prevented this effect and reduced NK insulin receptor expressions. Conclusion : Elevated insulin levels in F1 and F2 fibrosis enhances NK cell cytotoxic activity toward HSCs and prevents fibrosis progression by insulin receptors and downstream mammalian target of rapamycin and extracellular signal‐regulated kinase pathways. At more advanced stages of insulin resistance (F3 and F4 fibrosis), impaired NK cell activity rooted in low insulin receptor expression and or low serum insulin levels could further deteriorate fibrosis and may likely lead to cirrhosis development. ( Hepatology Communications 2018;2:285‐298)